Research on the stereotype of a Chinese or how Chinese are seen by Poles - Grabowska, Katarzyna (Myths and Stereotypes in the Collective Representations, 2019)
In international relations national stereotypes play a very crucial role. Since they have an influence on our subconscious level, they also decide about our sympathy or antipathy toward individual nations. Fields, German, Russian, Chinese etc. stereotypes make us project images which are built on the vision of a nation that was inherited by us in the process of growing up in a particular cultural environment.Based on research conducted in Poland and as well as my own research survey I will present how the eyes of Poles are presented by the Chinese.